Local Hotel Innovation in Post-Covid-19 Tourism Destinations: Typology, Models and Influence on Performance - Sudiksa, I Nyoman; Putra, I Nyoman Darma; Sunarta, I Nyoman; Mananda, I Gusti Putu Bagus Sasrawan (Devotion : Journal of Research and Community Service, 2023)
This study aims to explore innovations made by local hotels in post-COVID-19 tourism destinations, focusing on innovation typologies, implementation models, and their impact on operational and financial performance. A mixed approach was taken to this study. A qualitative approach was taken to determine the typology of local hotel innovations in Ubud tourism destinations. Data collection in a qualitative approach is carried out through interview activities, with qualitative descriptive analysis in the form of thematic analysis with a deductive approach. While the quantitative approach is carried out to build an innovation model based on customer engagement, employee contribution, the use of technology in creating innovation, and analyzing the influence of innovation on the performance of local hotels in Ubud tourist destinations through survey methods, and data analysis using SEM (Structural Equation Modelling) analysis to analyze structured correlations both relationships between indicators and relationships between variables. The results of this study are expected to provide an in-depth picture of how local hotels in tourism destinations creatively respond to post-COVID-19 challenges through innovation. This finding is expected to provide valuable insights for tourism industry players, governments, and researchers to understand the dynamics of innovation in the face of paradigm shifts in the post-pandemic era. The conclusions shows that Product-Process Innovation has the greatest influence on performance, while Organizational Innovation has the lowest effect on hotel performance.